2020
DOI: 10.3390/ijms21031079
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A (BPA)-Induced Changes in the Number of Serotonin-Positive Cells in the Mucosal Layer of Porcine Small Intestine—the Preliminary Studies

Abstract: Bisphenol A (BPA) is a substance used in the production of plastics which has a negative impact on many internal organs. Because BPA is normally toxic for the gastrointestinal (GI) tract, the intestine is especially vulnerable to the adverse effects of this substance. The aim of this investigation was to study the influence of two doses of BPA (0.05 mg and 0.5 mg/kg body weight/day) on the number of mucosal cells in the porcine small intestine and containing serotonin (5-hydroxytryptamine, 5-HT). During the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…BPA caused the decrease in the number of cholinergic neurons and intramural nerves. This observation is in line with the previous studies concerning fluctuations of neurotransmitters and/or neuromodulators in the autonomic nervous system supplying the uterus and small intestine in response to the impact of BPA [ 6 , 12 , 13 , 40 ]. Moreover, the recent investigations have reported that the number of cholinergic enteric nervous structures is also reduced during various pathological and toxic stimuli [ 13 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…BPA caused the decrease in the number of cholinergic neurons and intramural nerves. This observation is in line with the previous studies concerning fluctuations of neurotransmitters and/or neuromodulators in the autonomic nervous system supplying the uterus and small intestine in response to the impact of BPA [ 6 , 12 , 13 , 40 ]. Moreover, the recent investigations have reported that the number of cholinergic enteric nervous structures is also reduced during various pathological and toxic stimuli [ 13 , 42 , 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…Contrary to the intestine, where BPA may affect the motility, secretion, intestinal barrier, and neurochemical coding of neuronal cells and nerves in the ENS [ 12 , 13 , 40 ], knowledge about the influence of BPA on the stomach is extremely scarce. It is only acknowledged that BPA causes changes in the number of nitrergic enteric nerve cells in both types of gastric intramural plexuses [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, 60 observation fields were evaluated for each sample from each animal. The obtained data were pooled and analysed as comparison of mean value [ 31 ]. Statistical analysis was performed using Student’s t-test (GraphPad Prism v. 3.0, GraphPad Software Inc., San Diego, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…It recalls that 5-HT can be seen as an orchestrator of metabolism and cell interaction. Modification of 5-HT function should draw specific attention as indicated by Slawomir Gonkowski [4]. In his study performed in the porcine intestine, he found that the exposition of pigs to Bisphenol A, a substance used in the production of plastics, enhances the number of 5-HT cells along with the mucosal layer of the duodenum, jejunum, and ileum.…”
Section: Introductionmentioning
confidence: 99%